Sociocultural Factors and Offending Among a Nationally Representative Sample of U.S. Hispanic Men and Women: A Sex-Specific Analysis - Centelles, Vanessa (Crime & delinquency, 2025)
There is limited research on how sociocultural factors may relate to offending for adult Hispanic persons by gender. Using a nationally representative sample of U.S. Hispanic men and women, we used sex-specific models to examine the relationships of sociocultural factors (i.e., discrimination, acculturation, and ethnic identity) with offending and their respective moderating effects. Acculturation and discrimination were positively associated with violent and non-violent offending among men and women, with the effects largely invariant. Ethnic identity was only salient for women and non-violent offending. Acculturation contextualized discrimination for men at higher levels of non-violent offending, albeit no other interactions were notably significant. These are situated using discourse surrounding Hispanic gender norms and symmetry, and the importance of future research.